The Correlation between Students’ Self-Confidence and Speaking Ability - -, lutfi nur azizah (ENJEL: English Journal of Education and Literature, 2024)
The title of this research is “THE CORRELATION BETWEEN STUDENT'S SELF-CONFIDENCE AND SPEAKING ABILITY”. The objective of the research is to find out whether there is significant correlation or not between student’s self-confidence and speaking ability of sixth and eighth semester student of 2022-2023 academic year English Language Education Program Faculty of Teacher Training and Education Universitas Muhammadiyah Jember. The researcher use correlational research, quantitative nonexperimental research. The sample of this study is 33 students from sixth and eighth grade semester English Language Education Program Faculty of Teacher Training and Education Universitas Muhammadiyah Jember, which consists of 16 students from 6th semester and 17 students from 8th semester. The collecting data technique used a speaking test and a questionnaire. The results of this study show that there is a significant relationship between self-confidence and speaking ability.